Students’ Performance in Solving Problems Involving Fractions - Linda Vitoria; Fauzi Fauzi; Nadia Ananda (Proceedings of AICS - Social Sciences, 2017)
The concept of fraction is a fundamental mathematics subject that is repeatedly reported to be difficult for students to learn and for teachers to teach. Various articles on strategies to teach fractions have been presented, but students’ proficiency in dealing with fractions has not improved in general. This article describes a qualitative study conducted to assess students’ performance in solving a set of problems involving addition and subtraction of fractions. The students’ performances were analyzed according to the standard competence as inscribed in the Indonesian Curriculum Version Year 2013 for fifth grade students which was: capable of solving problems involving addition and subtraction of fractions with different denominators. A set of test was administered to twenty fifth-grade students at a primary school in Aceh, Indonesia. Result showed that the students’ understanding of addition and subtraction of fractions was poor: majority of the students knew the rule of addition and subtraction of fractions but only 45% executed the computation correctly, 25% students appeared to be struggling in finding the least common denominator when executing operations with fractions, none of the students reduced their fractions to lowest terms, and understanding word problems also proved to be a challenge to many of the students. This finding necessitates the importance of meaningful learning. Students need to experience fractions in a familiar context in order to be able to grasp conceptual and procedural understanding of fractions. Keywords:student performance, addition and subtraction of fractions.